Relationship between social support and schizophrenia relapse among patients with schizophrenia on follow-up at Amanuel Mental Specialized Hospital, Addis Ababa, Ethiopia: A case-control study - Samuel, Tinbete; Nigussie, Kabtamu; Mirkena, Yohannes; Azale, Telake (Frontiers in Psychiatry, 2022)
Background Severe mental illnesses affect about 4% of the adult population worldwide. The illness is highly related to the relapse rate and can cause cognitive, social, and functional deterioration in patients. While there are some factors that are known to be protective of the occurrence of relapse in schizophrenia, having good social support is found to be one of the strongest factors. Therefore, the aim of this study was to identify the association between relapse and poor social support in patients with schizophrenia. Methods With unmatched case-control (case—patients with schizophrenia with poor social support and controls—patients with schizophrenia with good social support), the study included 408 patients with schizophrenia on a follow-up at Amanuel Mental Specialized Hospital from March to May; 2020. The convenience sampling technique was used to draw the participants. Social support was assessed by the Oslo social support scale (Oslo-3), whereas Family Emotional Involvement and Criticism Scale and Medication Adherence Rating Scale-10 (MARS-10) were used to assess the emotion expressed and adherence to medication, respectively. Epidemiological Information (Epi Info) version 7 was used for data coding and entry, which were then exported to the Statistical Package for Social Sciences version 22 for analysis. Unconditioned binary logistic regression analysis and bivariate correlation analysis were carried out. Results Out of 408 samples, 396 participants, of which 194 were cases and 202 were controls, were included in the study with a response rate of 97.06%. The mean and standard deviation (SD) age of the participants was 36.06 ± 9.842 years. From 194 cases, 61.1% of them were reported to have poor social support. In multiple logistic regression, only social support was found to be statistically significant [p < 0.001, adjusted odds ratio (AOR) = 3.102, confidence interval (CI) (95%) = (1.985–4.848)]. Hence, the odds of having relapse were 3.102 higher in those who have poor social support when compared to those with good social support. Emotional involvement, financial problems, and stressful life events were found to indirectly affect relapse by having a negative correlation with social support. Conclusion The present study showed that there was a relationship between relapse and social support, and this indicates that social support can be a good predictor of schizophrenia relapse. The caregivers and clinicians of the patients should increase their support to the patients, while hospitals with mental health services have to encourage formation of better social support for the patients, including psychosocial interventions which will be performed to enhance the social support system.